Situation Report: Bulgaria, 21 November 1975 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Dismissals from the Editorial Board of Literaturna Misal? Support for Personal Plots and Criticism of Local Officials Shortcomings in Business Trips Abroad Again Criticized